Uwarunkowania i bariery finansowania projektów inwestycyjnych samorządu terytorialnego funduszami Unii Europejskiej - Sierak, Jacek (Conditions and Barriers of Financing Territorial Communities Investment Projects by European Union Funds, 2007)
Polish membership in the European Union opens new perspectives for additional co-financing sources of local and regional development. The usage of legal tenders which come from European Union Funds can contribute to acceleration of society and economy development of communities, improvement of social service standard, level of nature environment and cultural heritage. Making use of this chance depends on number and quality of investment projects declared for co financing from European Union Funds. A loi of threats which result from the need of fulfilling the European Union's supplementary rule are connected with financing investment projects. Condition for their realization is very good preparation and efficient investment realization using methods of strategic management of territorial community unit.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 457-466